Palatable Food Affects HPA Axis Responsivity and Forebrain Neurocircuitry in an Estrous Cycle-specific Manner in Female Rats. (1st August 2018) - Egan, Ann E.; Thompson, Abigail M.K.; Buesing, Dana; Fourman, Sarah M.; Packard, Amy E.B.; Terefe, Tegesty; Li, Dan; Wang, Xia; Song, Seongho; Solomon, Matia B.; Ulrich-Lai, Yvonne M.
Highlights: Limited sucrose intake (LSI) blunts the plasma ACTH response to restraint stress in female rats during proestrus/estrus. LSI does not blunt post-restraint plasma ACTH during the diestrus phase of the estrous cycle. Bayesian modeling is used with neuronal activation/plasticity markers to identify a brain network modified by LSI. The modeled network includes the BLA, NAc, PFC, and BST as likely being modified by LSI during proestrus/estrus. Abstract: Eating palatable foods can provide stress relief, but the mechanisms by which this occurs are unclear. We previously characterized a limited sucrose intake (LSI) paradigm in which twice-daily access to a small amount of 30% sucrose (vs. water as a control) reduces hypothalamic–pituitary–adrenocortical (HPA) axis responses to stress and alters neuronal activation in stress-regulatory brain regions in male rats. However, women may be more prone to 'comfort feeding' behaviors than men, and stress-related eating may vary across the menstrual cycle. This suggests that LSI effects may be sex- and estrous cycle-dependent. The present study therefore investigated the effects of LSI on HPA axis stress responsivity, as well as markers of neuronal activation/plasticity in stress- and reward-related neurocircuitry in female rats across the estrous cycle. We found that LSI reduced post-restraint stress plasma ACTH in female rats specifically during proestrus/estrus (P/E). LSI also increased basal (non-stress) FosB/deltaFosB- and pCREB-immunolabeling in the basolateral amygdala (BLA) and central amygdala specifically during P/E. Finally, Bayesian network modeling of the FosB/deltaFosB and pCREB expression data identified a neurocircuit that includes the BLA, nucleus accumbens, prefrontal cortex, and bed nucleus of the stria terminalis as likely being modified by LSI during P/E. When considered in the context of our prior results, the present findings suggest that palatable food reduces stress responses in female rats similar to males, but in an estrous cycle-dependent manner. Further, the BLA may contribute to the LSI effects in both sexes, whereas the involvement of other brain regions appears to be sex-dependent.